2023
DOI: 10.1101/2023.01.24.525280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telomerase reactivation induces progression of mouse BrafV600E-driven thyroid cancers without telomere lengthening

Abstract: Mutations in the promoter of the telomerase reverse transcriptase (TERT) gene are the paradigm of a cross-cancer alteration in a non-coding region. TERT promoter mutations (TPMs) are biomarkers of poor prognosis in several tumors, including thyroid cancers. TPMs enhance TERT transcription, which is otherwise silenced in adult tissues, thus reactivating a bona fide oncoprotein. To study TERT deregulation and its downstream consequences, we generated a Tert mutant promoter mouse model via CRISPR/Cas9 engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Studies of BC and BTC mouse models indicated an essential role of TERT in the progression of thyroid cancer into the advanced stage. A Tert promoter mutation and BRAF V600E expression murine model has recently been disclosed, and the transition from PTC to PDTC is also captured in Tert promoter mutant mice ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of BC and BTC mouse models indicated an essential role of TERT in the progression of thyroid cancer into the advanced stage. A Tert promoter mutation and BRAF V600E expression murine model has recently been disclosed, and the transition from PTC to PDTC is also captured in Tert promoter mutant mice ( 56 ).…”
Section: Discussionmentioning
confidence: 99%